Political violence and necropolitics in Omar Shahid Hamid’s The Prisoner - Ahmed, Toqeer (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article examines violence and necropolitical experiences in the management of life and death in Pakistan’s largest city, Karachi and its representation by Omar Shahid Hamid in his debut novel The Prisoner (2013). Pakistan’s western border and the largest city Karachi have long been epicentres of violent actions in the backdrop of wars (for instance, the Soviet and the ‘War on Terror’) in neighbouring Afghanistan. The relationship of governing authorities with violence and necropolitics is analysed in the light of critical approaches from the works of Michael Foucault (2008), Achille Mbembe (2001 & 2003), Giorgio Agamben (1998 & 2005), and Judith Butler (2004). Through the analysis of the fictional narrative, this paper examines local and global deployment of various strategies of occupation, domination and subjugation that aims to manage human bodies through social, economic, political and religious discourses. This article argues that violence and death are used as a means of control over human bodies as represented in the novel, a situation in which some lives are disposable and are reducible to ‘bare life’ by state and nonstate actors. Against this backdrop, the article highlights how some lives matter more than others in Karachi’s political landscape. This article also suggests that the landscape in The Prisoner is an embodiment of what Agamben called the ‘state of exception’, a state where (some) people are deemed unworthy of life, and are therefore, removed. It is hoped that this article will be useful to understand complex issues of Karachi.